2020
DOI: 10.29076/issn.2528-7737vol13iss33.2020pp85-95p
|View full text |Cite
|
Sign up to set email alerts
|

Generación de tecnologías para incrementar la productividad del algodón Gossypium hirsutum L. en Manabí, Ecuador

Abstract: El objetivo de esta investigación fue generar tecnología para la producción de algodón. En ese sentido se evaluó la respuesta de dos variedades (DP-Acala 90 y Coker) a dos densidades de siembra (62.500 y 50.000 plantas ha-1) y dos programas de manejo agronómico (tecnología INIAP y tecnología clásica). El ensayo se realizó en la época seca de 2018, en la Estación Portoviejo del INIAP (01°09´51”S, 80°23´24”W, 60 msnm y 26,4 °C, 81% de HR, 851,57 mm). Se formaron ocho tratamientos, dispuestos en un Diseño de Bloq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
(12 reference statements)
3
5
0
1
Order By: Relevance
“…While in plots treated with lambda cyhalothrin + thiamethoxam, 1 to 2 individuals plant -1 were observed, under untreated plot, the number of individuals increased from 5 to 11 (Figure 6), resulting significantly higher than this last treatment (Table 2). The results are similar to those reported by Cañarte-Bermudez et al (2020) who for the same area and months of evaluation reported a high incidence of Dysdercus spp. associated with the fiber formation stage.…”
Section: The Cotton Strainers Dysdercus Sppsupporting
confidence: 91%
See 4 more Smart Citations
“…While in plots treated with lambda cyhalothrin + thiamethoxam, 1 to 2 individuals plant -1 were observed, under untreated plot, the number of individuals increased from 5 to 11 (Figure 6), resulting significantly higher than this last treatment (Table 2). The results are similar to those reported by Cañarte-Bermudez et al (2020) who for the same area and months of evaluation reported a high incidence of Dysdercus spp. associated with the fiber formation stage.…”
Section: The Cotton Strainers Dysdercus Sppsupporting
confidence: 91%
“…Of these, Coleomegilla maculata De Geer together with Zelus sp., were the most abundant species (Table 3). The latter species of predators had previously been reported in the area (Cañarte-Bermudez et al, 2020). The results showed a significantly lower number of predators in treated plants with lambda cyhalothrin + thiamethoxam (Table 3).…”
Section: Predatorssupporting
confidence: 65%
See 3 more Smart Citations